2019
DOI: 10.20945/2359-3997000000193
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of morbidities and mortality in acromegaly

Abstract: Acromegaly is a systemic disease associated with increased morbidity, presenting cardiovascular, metabolic, respiratory, neoplastic, endocrine, articular and bone complications. Most of these comorbidities can be prevented or delayed with adequate disease treatment and, more recent studies with the use of modern treatments of acromegaly, have shown a change in the severity and prevalence of these complications. In addition, acromegaly is associated with increased mortality, but recent studies (especially those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 60 publications
0
29
1
8
Order By: Relevance
“…Over the past decade, disease control has improved due to enhanced therapeutic strategies, leading to reversal of the increased mortality risk traditionally associated with acromegaly [38][39][40]. A meta-analysis showed increased mortality in 17 studies published before 2008 (standardized mortality ratio [SMR] 1.76; 95% CI 1.52, 2.4; p < 0.00001), but mortality was strikingly not different from the general population in 9 studies published after 2008 (SMR 1.35; 95% CI 0.99, 1.85) [39].…”
Section: What's Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, disease control has improved due to enhanced therapeutic strategies, leading to reversal of the increased mortality risk traditionally associated with acromegaly [38][39][40]. A meta-analysis showed increased mortality in 17 studies published before 2008 (standardized mortality ratio [SMR] 1.76; 95% CI 1.52, 2.4; p < 0.00001), but mortality was strikingly not different from the general population in 9 studies published after 2008 (SMR 1.35; 95% CI 0.99, 1.85) [39].…”
Section: What's Newmentioning
confidence: 99%
“…Excess mortality reported in earlier studies was primarily due to cardiovascular diseases (SMR 2.95; 95% CI 2.35, 3.55), including ischemic heart disease (SMR 2.00; 95% CI 1.35, 2.66) and cerebrovascular disease (SMR 3.99; 95% CI 2.42, 5.55), with a lesser effect from malignancy (SMR 1.76; 95% CI 1.27, 2.26) [40]. In recent studies, cancer has been reported as the leading cause of death in acromegaly, likely related to longer life expectancy due to better control of the disease and its related comorbidities rather than a specific increased risk of cancer [38,39,41]. A nationwide cohort from Taiwan including 1195 patients followed from 1997 to 2013 showed 87 newly diagnosed cancers, with an incidence rate of 10.6 per 1,000 person-years [42], or a standardized incidence ratio of 1.91.…”
Section: What's Newmentioning
confidence: 99%
“…Early diagnosis of acromegaly and its treatment is mandatory to avoid comorbid diseases and further complications leading to premature death. Radical surgery as well as pharmacological control of disease activity decrease mortality to that observed in the normal population ( 7 , 8 ). Moreover, a lot of acromegaly patients suffer from decreased life quality despite cured or well-controlled disease activity ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…При отсутствии адекватного лечения летальность больных акромегалией в 2-4 раза превышает средний показатель в популяции. К независимым предикторам преждевременной смерти относят онкологические заболевания, кардиоваскулярные нарушения, артериальную гипертензию, сахарный диабет, большую продолжительность активной стадии [1][2][3][4][5].…”
Section: обоснованиеunclassified